The TLR-NF-kB axis contributes to the monocytic inflammatory response against a virulent strain of Lichtheimia corymbifera, a causative agent of invasive mucormycosis - Montaño, Dolly E.; Hartung, Susann; Wich, Melissa; Ali, Rida; Jungnickel, Berit; von Lilienfeld-Toal, Marie; Voigt, Kerstin (Frontiers in Immunology, 2022)
Invasive mucormycosis (IM) is a life-threatening infection caused by the fungal order Mucorales, its diagnosis is often delayed, and mortality rates range from 40-80% due to its rapid progression. Individuals suffering from hematological malignancies, diabetes mellitus, organ transplantations, and most recently COVID-19 are particularly susceptible to infection by Mucorales. Given the increase in the occurrence of these diseases, mucormycosis has emerged as one of the most common fungal infections in the last years. However, little is known about the host immune response to Mucorales. Therefore, we characterized the interaction among L. corymbifera—one of the most common causative agents of IM—and human monocytes, which are specialized phagocytes that play an instrumental role in the modulation of the inflammatory response against several pathogenic fungi. This study covered four relevant aspects of the host-pathogen interaction: i) The recognition of L. corymbifera by human monocytes. ii) The intracellular fate of L. corymbifera. iii) The inflammatory response by human monocytes against the most common causative agents of mucormycosis. iv) The main activated Pattern-Recognition Receptors (PRRs) inflammatory signaling cascades in response to L. corymbifera. Here, we demonstrate that L. corymbifera exhibits resistance to intracellular killing over 24 hours, does not germinate, and inflicts minimal damage to the host cell. Nonetheless, viable fungal spores of L. corymbifera induced early production of the pro-inflammatory cytokine IL-1β, and late release of TNF-α and IL-6 by human monocytes. Moreover, we revealed that IL-1β production predominantly depends on Toll-like receptors (TLRs) priming, especially via TLR4, while TNF-α is secreted via C-type lectin receptors (CTLs), and IL-6 is produced by synergistic activation of TLRs and CTLs. All these signaling pathways lead to the activation of NF-kB, a transcription factor that not only regulates the inflammatory response but also the apoptotic fate of monocytes during infection with L. corymbifera. Collectively, our findings provide new insights into the host-pathogen interactions, which may serve for future therapies to enhance the host inflammatory response to L. corymbifera